Exploring resistance changes of porous carbon upon physical adsorption of VOCs. (May 2019) - Kante, Karifala; Florent, Marc; Temirgaliyeva, Ainura; Lesbayev, Bakhytzhan; Bandosz, Teresa J.
Abstract: Electrical response of nanoporous carbon upon exposure to VOCs was tested. For this purpose, commercial wood-based chemically activated carbon was chosen owing to its high surface area, heterogeneity of its pore sizes and rich surface chemistry. When carbon chips were exposed to various concentrations of toluene, chloroform, and methanol vapors visible changes in resistivity were observed and these changes were linked to the properties of the adsorbates and the extent of an adsorption process. The findings support the feasibility of both: adsorption-based VOCs sensing and electrical response-based adsorption measurements on porous carbons.